Gambaran Pengetahuan Ibu Tentang Imunisasi Dasar Lengkap Di Puskesmas Belo - Hartina, Asniah (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
Immunization is the most effective and efficient public health effort in preventing diseases and reducing mortality such as smallpox, polio, tubercolosis, hepatitis B, diphtheria, measles, rubella and congenital rubella syndromes (CRS), tetanus, pneumonia and meningitis (inflammation of the lining of the brain). This study aims to analyze maternal knowledge about basic immunization in infants aged 0-11 months in the working area of Belo Health Center of Belo District in 2023. Sampling technique in the form of accidental sampling. The population consisted of 114 respondents and a sample of 89 respondents. The results of the study showed that Most mothers had sufficient knowledge i.e. Mothers aged < 20 tahun 3 ibu (100%), Ibu umur 20 — 35 tahun 29 ibu (60,4%), ibu berumur> 35 years 6 mothers (37.5%), Parity 1 mothers (65%), parity mothers 2-3 i.e. 18 mothers (48.6%), parity mothers >3 i.e. 3 mothers (75%), Mothers who gained sufficient access to information 5 mothers (41.7%) and Mothers who gained less information access 33 mothers (60.6%) 0%)